The Effect of Financial Inclusion and Financial Literacy Against Sharia Banking Stability at Bank Syariah Indonesia - Syahira Nabila; Kamilah K; Laylan Syafina (IAIN Palopo, 2023)
The existence of financial inclusion, access to formal financial services such as savings, credit, and other products is very helpful for marginalized and low-income groups to improve welfare. Because financial markets are the heart of the economy that can contribute to people's economic welfare. This type of research uses quantitative methods with descriptive statistical research properties. Methodology used documentation methods and literature study. The data used is secondary data, namely financial statements. The processing of this research data uses the SPSS 20 program. The results showed that partial financial inclusion has a significant effect on banking stability. Partial financial literacy does not have a significant effect on banking stability. Simultaneously, financial inclusion and financial literacy affect the stability of Indonesia's sharia banking in 2019-2021. The results of the coefficient of determination test can be found that the value of Adjusted R Squared is 0.220 or 22.0%. This shows the ability of the independent variable in the study to explain the dependent variable by 22.0%, while the rest is explained by other variables by 78.0% which are not included in the study